2011
DOI: 10.1007/s00134-011-2194-4
|View full text |Cite
|
Sign up to set email alerts
|

Deadspace ventilation: a waste of breath!

Abstract: Problems with ventilatory efficiency results in abnormal CO(2) clearance. Measuring deadspace ventilation should be the most reliable method of monitoring ventilatory efficiency in mechanically ventilated patients. Since its first description by Bohr in the late 19th century to the current use of single-breath test for volumetric CO(2), our understanding of the physiological deadspace has vastly improved. Yet indices of oxygenation seem to be the mainstay when instigating or fine-tuning ventilatory strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 67 publications
0
32
0
2
Order By: Relevance
“…An arterial blood gas was obtained at the time of expired gas analysis. Measured dead-space fraction was calculated using the Enghoff modification to the Bohr equation (26): VDVT=false(PaCO2PECO2false)PaCO2 where PaCO 2 and P E CO 2 represent partial pressure of CO 2 in arterial blood and expired gas, respectively. All measurements were made prior to study interventions.…”
Section: Methodsmentioning
confidence: 99%
“…An arterial blood gas was obtained at the time of expired gas analysis. Measured dead-space fraction was calculated using the Enghoff modification to the Bohr equation (26): VDVT=false(PaCO2PECO2false)PaCO2 where PaCO 2 and P E CO 2 represent partial pressure of CO 2 in arterial blood and expired gas, respectively. All measurements were made prior to study interventions.…”
Section: Methodsmentioning
confidence: 99%
“…The last decade has seen many advancements in care for patients with the Acute Respiratory Distress Syndrome (ARDS) including improvements in ventilator management,[1, 2] noninvasive mechanical ventilation strategies,[35] sepsis management,[6] and intensive care unit system changes. [7, 8] More patients with ARDS are now surviving to hospital discharge, a phenomenon that has been reported in both observational studies and randomized trials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the value of V D /V T in critically ill patients in both prognostication and disease progression in conditions such as acute respiratory distress syndrome (ARDS) [1-4]. Yet due to the complexity or equipment costs associated with its calculation, V D /V T is seldom measured in daily intensive care unit (ICU) practice [5,6]. The partial pressure of oxygen in arterial blood/fractional concentration of inspired oxygen (PaO 2 /FiO 2 ) is a simple ratio that describes the adequacy of oxygenation and is widely used in daily practice despite being a poor predictor of outcome [7].…”
Section: Introductionmentioning
confidence: 99%